Perancangan Sistem Pengolahan Data Nilai Siswa berbasis Java di SMP At-Taqwa Kec. Sawah Besar Jakarta - Muhammad Aland Wahyu Andrian (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2019)
Technological developments have penetrated all areas of life very rapidly and facilitated many activities. Computers are one of the devices that are needed for data processing, so that the data processed can be effective and efficient in providing information needed by an organization. School becomes one of the means in the world of education, also requires a computer in carrying out its activities to solve problems faced and reduce the level of human error in entering data. School education is inseparable from student data and the academic values of their students. At junior high school, the data processing value of students still uses manual methods, namely using the ms program. excel and ms. just word. So that the processing and storage of values are done manually, so much precision and time are needed for the report making process. For this reason, it is necessary to design a student value data processing system with the support of the java swing programming language and mysql database.